Jesuits and Astrology: Print versus Manuscript - Ribeiro, Luís Campos (Journal of Jesuit studies, 2023)
Astrology played an important part in early modern European culture, as a fundamental part of both mathematical and astronomical traditions. During the same period, the Society of Jesus built their global educational enterprise, which included a proven expertise in mathematical and astronomical study. Although insufficiently acknowledged in Jesuit historiography, astrology formed an important part of this scientific project. Several Jesuit authors engaged in the study, teaching, and practice of astrology. From the mathematics curriculum of the Roman College to the Jesuit astrology classes in Portugal and Spain, the present article discusses astrology’s presence in early modern Jesuit publications. It examines the discussion of astrology in the Society’s scientific works, highlights the sharp contrast between the printed word and the manuscript tradition, and demonstrates how the latter provides a better guide to the role of astrology as part of Jesuit science.